2013
DOI: 10.1007/s11999-012-2727-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone Turnover Markers Do Not Predict Stress Fracture in Elite Combat Recruits

Abstract: Level II prognostic study. See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
1
18
0
3
Order By: Relevance
“…In contrast, measurements of u-NTX obtained the day after moderate exercise were reported to be no different from measurements obtained before exercise [28]. Although it was reported that bone metabolism markers are not suitable prediction markers for stress fracture [29], the bone metabolism marker used in the previous study was a serum marker (TRACP-5b, CTX), and u-NTX was not measured. Based on previous studies, TRACP-5b increases when there is a history of stress fracture, but it may not be reliable on the onset of stress fracture [27], whereas in our study u-NTX became higher when stress fracture develops, indicating that there are certain characteristic bone resorption markers.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, measurements of u-NTX obtained the day after moderate exercise were reported to be no different from measurements obtained before exercise [28]. Although it was reported that bone metabolism markers are not suitable prediction markers for stress fracture [29], the bone metabolism marker used in the previous study was a serum marker (TRACP-5b, CTX), and u-NTX was not measured. Based on previous studies, TRACP-5b increases when there is a history of stress fracture, but it may not be reliable on the onset of stress fracture [27], whereas in our study u-NTX became higher when stress fracture develops, indicating that there are certain characteristic bone resorption markers.…”
Section: Discussionmentioning
confidence: 83%
“…2008, Yanovich et al. 2013). In our study, all 3 markers of bone formation—bone-specific alkaline phosphatase, osteocalcin, and P1NP—were elevated in patients with stress fractures, but we ascribe these elevations mainly to ongoing fracture healing, where elevated levels can be seen even after 1 year (Ingle et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ruohola et al found no difference in TRAP between stress fractured military recruits and controls, though recruits with proportionally increasing TRAP during training were more likely to suffer a stress fracture [20]. A recent study in Israeli male military recruits (n = 69) found no differences in CTx and two other bone turnover markers between stress fractured recruits and non-fractured recruits [22]. Moreover, in a twelve month prospective study in athletes, measurements of bone turnover were found not to be useful in predicting the likelihood of stress fracture occurrence [38].…”
Section: Bone Resorptionmentioning
confidence: 95%
“…Previous studies have reported conflicting findings with regards to longitudinal changes in bone turnover markers during military training, as well as with respect to differences between stress fracture cases and controls [19][20][21][22]. Therefore the relevance of bone turnover markers in predicting stress fracture risk remains unclear.…”
Section: Bone Turnover Markersmentioning
confidence: 99%